The potential of poultry processing waste to generate renewable energy using Microbial Fuel Cells (MFCs) - Abdul Syukor, Abd Razak; Jadhav, Pramod Chandrakant; Muhamad Hamed, Saharani; Suryati, Sulaiman; Mohd Nasrullah, Zulkifli (Universiti Malaysia Pahang, 2020)
Microbial Fuel Cell (MFCs) is a concept of applying microorganisms as catalyst in fuel cell. It works by oxidizing the electron and proton and transferred to the anode chamber under anoxic conditions to produce electricity. Microbial production of electricity might become an important form of bioenergy in future because MFCs extracting electric current from a wide range of soluble or dissolved complex organic wastes and renewable biomass. The poultry processing waste is collected from the Pusat Pemprosesan Ayam Kuantan. The double chamber MFC with three different concentration of substrate is used to generate the renewable energy from the waste. Analysis of data was performed by using a 1-way analysis-of-variance (1-way ANOVA). The significant ANOVA (P<0.05) studies shown the different in values of the monitored 4 parameters which indicates the data obtained is accurate. In this study, result analysis reveals that poultry processing waste is able to use as substrate in MFC hence able to produced energy. The maximum voltage that able to produce is 0.389V by using 1.2g of substrate concentration. Meanwhile, the MFC operation also is able to remove BOD and COD. These high levels of removal efficiency demonstrate the MFC system’s ability to treat poultry processing waste with the added benefits of generating energy.